Genome-wide identification of the OfMYC gene family and putative involvement of OfMYC10/16 in petal senescence via an EIL–ERF–ROS regulatory module - Hui Xia; Qinyu Yan; Ting Zhang; Jie Yang; Hongguo Chen; Xuan Cai; Jingjing Zou; Zeqing Li; Xiangling Zeng; Yingting Zhang (Postharvest Biology and Technology, 2026)

Effects of two enzyme–microbe co-fermented feed formulations on growth performance, ruminal fermentation, serum metabolome, and gastrointestinal microbiota in mid-fattening simmental heifers - Keren Yang; Ting Liu; Hanfang Zeng; Zhenling Wu; Xuanwei Lv; Daiwei Li; Zhiwen Xu; Liming Wei; Dehai An; Shicheng Wang; Chen Zheng (Animal Feed Science and Technology, 2026)

In situ formation of chemically integrated and mechanically interlocked interphases enables robust epoxy-copper adhesion - Ting Xin; Zeyu Zheng; Zuo Li; Yue Wu; Yang Liu; Binbin Zhou; Jibao Lu; Xiaoliang Zeng; Fan Yang; Gang Li; Rong Sun; Pengli Zhu (Chemical Engineering Journal, 2026)

Persistent carbon composition converges across vegetated and unvegetated coastal soils despite contrasting stabilization pathways - Yuan Li; Joeri Kaal; Chuancheng Fu; Dongdong Zhang; Peter I. Macreadie; Ting Wang; Lin Zeng; Feilong Hu; Guangxuan Han; Yongming Luo (Water Research, 2026)

The SNARE gene CwSYP121 enhances Ca²⁺ secretion and calcium tolerance of Ceratostigma willmottianum by modulating vesicle trafficking - Cailei Liu; Long Guo; Yirui Li; Wenjun Li; Qinxiao Zeng; Xuan Liu; Hanbing Cai; Jiani Li; Qibing Chen; Ting Lei; Suping Gao (Plant Science, 2026)

Gradient sulfur-vacancy engineering of MoS2 for selective non-radical peroxymonosulfate activation: Toward enhanced interference resistance in complex water matrix - Xuexia Guo; Ting Li; Huinan Zhao; Wenbin Huang; Lu Zeng; Zhangnan Yao; Shuanghong Tian; Chun He (Journal of Environmental Chemical Engineering, 2026)

Targeting ACTG1 alleviates isoproterenol-induced cardiac injury by regulating endothelial-to-mesenchymal transition - Xianghui Zeng; Dian Wang; Hao Yang; Canqun Li; Ting Xiong; Ting Lu; Lu Dai; Feng Chen; Zhenfang Liu; Xing Li (Journal of Molecular Histology, 2026)

Single-cell multi-omics dissects transcript isoform and immune repertoire dynamics in human immunosenescence - Yuhui Zheng; Ze-Hui Ren; Yafei Yang; Wenteng Liu; Fupeng Li; Yajun Zuo; Tao Zeng; Xue Wang; Xiumei Lin; Xinyue Zhu; Baibing Guan; Wenwen Zhou; et al. (Science China Life Sciences, 2026)

Complete genome sequence of a novel Pseudomonas sp. GW-45 isolated from Antarctic Ardley cove showing DMSP degradation capability - Yi-He Zhang; Yong-Qiang Hu; Zuo-Qi Wang; Chun-Yang Li; Ting Hu; Zhong Hu; Yin-Xin Zeng (Marine Genomics, 2026)

Systematic cadmium isotope fractionation between the organic and mineral fractions of soils - Jiawen Zhou; Tingting Mu; Ting Gao; Rebekah E.T. Moore; Mark Rehkämper; Yufang Sun; Zhen Zeng; Xinyang Li; Shijin Guo; Tong Zhou; Longhua Wu; Yongming Luo (Journal of Hazardous Materials, 2026)

RNA demethylase CsALKBH8 enhances postharvest disease resistance of citrus fruit against penicillium digitatum via m6A-mediated transcript regulation - Ting Li; Lingqi Yue; Mengting Liu; Jing Zeng; Ying Li; Jiechun Peng; Guoxiang Jiang; Xuewu Duan (Food Research International, 2026)

“Lotus leaf meets nacre”: a dual biomimetic approach to creating highly humidity-stable films with exceptional barrier properties for food packaging - Ningkang Deng; Jinsong Zeng; Pengfei Li; Junzhang Wu; Jianqiao Su; Zhiqiang Gong; Yuan Peng; Ting Yao; Jinpeng Li; Daxian Cao; Bin Wang; Jun Xu; et al. (Food Chemistry, 2026)

Serendipita promotes seed germination and seedling development of the endangered orchid Mengzia foliosa under in vitro conditions - Xinhua Zeng; Yulin Pu; Shanmin Li; Qiaoning Ren; Chao Hu; Kai Jiang; Ting Guo; Qingjun Huang; Weichang Huang (Symbiosis, 2026)

Better representation of linear features in species distribution models: Mapping the distribution of the Scaly-sided Merganser (Mergus squamatus) - Yangsirui Zhang; Peizhong Liu; Lixing Gu; Li Wen; Ying He; Zijian Wang; Liangjun Zhou; Ting Lei; Cai Lu; Qing Zeng; Guangchun Lei (Journal of Environmental Management, 2026)

Maternal Bifidobacterium bifidum BD-1 supplementation during late gestation modulates offspring gut microbiota succession and responses to DSS-induced acute colitis in a delivery-mode-dependent manner - Chenrui Peng; Chang Lu; Xiaoting Li; Lunpu Zhang; Yao Zeng; Xiaona Wu; Ting Wu; Fang He; Xi Shen (Food Bioscience, 2026)

Spinel LiMn2O4 stabilized by Fe/Sb co-doping mediated MnO bond modulation for high-efficiency lithium extraction from brine - Wenjie Fan; Luxiang Ma; Huifang Li; Wencheng Pan; Xin Zeng; Ting Li; Zhixiang Li (Desalination, 2026)

Iodine vacancy-engineered BiOI steering selective singlet oxygen generation for high-flux antibiotic degradation with peroxyacetic acid activation - Yuchen Chu; Ting Zhou; Yuxi Zeng; Siying He; Jiawei Yue; Wenjun Wang; Yang Yang; Ziwei Wang; Fanzhi Qin; Hongda Liu; Xiaoming Li; Jie Liang; et al. (Chemical Engineering Journal, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

PD-1/PD-L1 inhibitor induces systemic inflammation and alters cardiac lipid metabolism in C57BL/6 J mice - Cong Ye; Zhi-Ting Jiang; Chen Yan; Xin-Ran Li; Yu-Hua Zhu; Ling-Yu Zeng; Lan Luo (Human Cell, 2026)

WITHDRAWN: Corrigendum to "H2S-releasing versatile hydrogel dressing with potent antimicrobial, anti-inflammatory, epithelialization and angiogenic capabilities for diabetic wound healing" [Chem. Eng. J. 469 (2023) 143398] - Jiale Chen; Zhixiang Mu; Dongfan Chen; Chen Huang; Ting Jin; Lin Li; Youyun Zeng; Qiang Zhou; Yanmei Zhang; Hongli Mao; Hui Deng; Xinkun Shen; et al. (Chemical Engineering Journal, 2026)

Correction: Stem Cell-Derived Exosomes Improve Neurological Dysfunction in a Rat Model of Moderate-to-Severe Cerebral Palsy - Tingting Peng; Huijuan Lin; Xiaoli Zeng; Yunlan Xie; Jie Luo; Lingjie Zhang; Shiya Huang; Zhiyi Ye; Xiaolin Guo; Wen Le; Mingtong Zhang; Wenhui Li; et al. (Stem Cell Reviews and Reports, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

Biochar-mediated microbial community and functional shifts regulate soil organic carbon fractions, enhancing carbon accumulation and stabilization in a subtropical plantation soil - Ting Li; Hongzhi Yang; Yuxin Tan; Mengzhu Jiang; Dechao Wu; Xiaoyong Chen; Wensheng Liu; Yelin Zeng; Kuan Peng; Yonghong Wang; Chan Chen; Guangjun Wang; et al. (Applied Soil Ecology, 2026)

Response of greenhouse gas emissions, nitrogen loss and microbial communities to the presence of conventional and biodegradable microplastics in soil - Wenxu Li; Mengxiao Li; Jiaju He; Zhenyu Huang; Jian Zeng; Christopher W.N. Anderson; Minghua Zhou; Cheng Zhang; Xuesong Gao; Di Zhao; Ting Lan (Applied Soil Ecology, 2026)

Epigenetic activation of lignin biosynthesis by CsJMJ16 confers enhanced resistance to Penicillium digitatum in citrus - Jing Zeng; Ting Li; Mengting Liu; Xiaoyan Duan; Jiechun Peng; Zhiwei Li; Guoxiang Jiang; Yueming Jiang; Xuewu Duan (Postharvest Biology and Technology, 2026)

Trade-off between quantity and quality: Coal waste particle size regulates composting humification via biotic and abiotic pathways - Juan Zeng; Jiannan Li; Ting Li; Zixu Zhang; Jie Ren (Journal of Environmental Chemical Engineering, 2026)

Active site-directed tandem catalysis on Pt-loaded nitrogen-rich carbon for driving piezo-synthesis of hydrogen peroxide and in-situ utilization for emerging contaminants removal - Huinan Zhao; Ting Li; Wei Liu; Kaiwen Wang; Yanhong Lu; Lu Zeng; Jia He; Lingling Hu; Chun He (Chemical Engineering Journal, 2026)

Seepage Characteristics and Heat Transfer Law of Coal Body by Liquid Nitrogen Fracturing Under Stress Disturbance Condition - Lei Zhang; Shipan Zeng; Ting Ren; Cun Zhang; Xijian Li; Songzhao Li (Natural Resources Research, 2026)

Characterization and source apportionment of halogenated organic pollutants in sediments from the Daya Bay, South China Sea - Ren-Jie Shang; Jian-Fang Hu; Ming-Yang Liu; Yao Xiao; Yi-Ting Zeng; Li-Tian Huang; Ping-An Peng (Marine Pollution Bulletin, 2026)

Inhibitory effect of pulsed electric field pretreatment on acrylamide formation in air-fried French fries and its mechanism - Jian Li; Yue-Wei Huang; Yi-Tong Li; Shi-Yin Luo; Wei-Yan Xiong; Jin-Hua Wang; Jun-Hu Cheng; Ting-Shi He; Xin-An Zeng (Food Research International, 2026)

Stem Cell-Derived Exosomes Improve Neurological Dysfunction in a Rat Model of Moderate-to-Severe Cerebral Palsy - Tingting Peng; Huijuan Lin; Xiaoli Zeng; Yunlan Xie; Jie Luo; Lingjie Zhang; Shiya Huang; Zhiyi Ye; Xiaolin Guo; Wen Le; Mingtong Zhang; Wenhui Li; et al. (Stem Cell Reviews and Reports, 2026)

Metabolomic changes following PMSG-induced estrus synchronization in Qianbei Ma goats - Feng-Xin Qiao; Yong-Hong Ju; Xiao-Dong Wang; Peng-Cheng An; Quan Ji; Rui-Yang Li; Ting-Ji Zeng; Qing Liu; Dai-Yue Zhang; Zu-Han Feng; Mao-Sheng Cao; Xiang Chen (Animal Reproduction Science, 2026)

Peptidomics Landscape of Intrahepatic Cholestasis of Pregnancy and its Molecular Mechanism Investigation - Piaopiao Huang; Xinrun Zhuang; Li Bao; Ting Liu; Wei Gu; Weijian Zeng (Cell Biochemistry and Biophysics, 2026)

Regulation of EMT and cholangiocarcinoma metastasis by KIN17 through the mTOR signaling pathway - Yuxia Yang; Qianying Luo; Chuhong Huang; Xiaocong Lin; Lok Ting Chu; Qiuyan Li; Jinjing Tang; Tao Zeng (Molecular and Cellular Biochemistry, 2026)

The transcription factor BRN2 confers cadmium tolerance by regulating SAM1 expression in Arabidopsis - Su Li; Jing Huang; Jia Qi Li; Chuan Jin Shan; Ren Fang Shen; Da Li Zeng; Jin Chen; Xian Jiao Guan; Xiao Fang Zhu; Ting Wu Liu; Yong Gang Xu (Plant Science, 2026)

Novel approach to binary protein construction via pulsed electric field-induced unfolding: Comprehensive enhancement of chickpea protein properties - Yongxin Teng; Xindong Xu; Boru Chen; Rui Wang; Ting Zhang; Xiangwei Zhu; Yonghui Li; Zhong Han; Xin-An Zeng (Food Hydrocolloids, 2026)

Understanding the role of C5a/C5aR1-mediated complement activation pathway in tumor progression and therapy resistance - Lemei Zheng; Jianxia Wei; Mengna Li; Changning Xue; Qingqing Wei; Zubing Wu; Xiaolong Li; Ting Zeng; Huizhen Xin; Wei Xiong; Hongyu Deng; Ming Zhou (Science China Life Sciences, 2026)

Physiological and Secondary Metabolism of Dendrobium nobile Lindl in Response to High Temperature Stress - Linlong Xu; Yijun Fan; Xueyan Tan; Jie Ma; Ting Li; Siyu He; Hui Wang; Liangjie Zhu; Le Zeng; Aoxue Luo (Journal of Plant Growth Regulation, 2026)

Onset timing and palaeoenvironmental records of Carnian Pluvial Episode (Late Triassic) in southwestern Guizhou, China - Shi-Xin Li; Zhi-Heng Ma; Xi Zhang; Wei Yang; Jian-Li Zeng; Mihai Emilian Popa; Kai-Nan Mao; Ting-Shan Zhang (Palaeoworld, 2026)

Associations of paraben exposures measured by repeated urinary biomarkers with sperm DNA damage and apoptosis - Xiu-Ting Li; Yu Miao; Min Zhang; Jia-Yue Zeng; Peng-Hui Liu; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; Ning Zhang; Long Ge; Han-Qin Ye; Pan-Pan Chen; et al. (Environmental Research, 2026)

Performance and mechanism of engineered oxygen-vacancy CuCo-spinel nanorods for activating peroxymonosulfate toward contaminant remediation - Yuan Pan; Xiansheng Zhang; Xinyi Huang; Teng Li; Yunze Wang; Ruilin Cao; Jin Zeng; Ting Wu; Shaobo Liu; Zhifeng Liu (Chemical Engineering Journal, 2026)

The correlation between social support and hopelessness among cancer survivors: a meta-analysis - Lu-Ting Shen; Jian-Zeng Lan; Attiq-Ur-Rehman; Wei Li; Meng-Wei Ge; Rui Feng; Kang Zhong; Si-qi Gao; Hong-Lin Chen (Cancer Causes & Control, 2026)

Optimizing soil microbial functions under long-term straw return enhances nutrient acquisition, thereby improving nutrient availability and crop productivity in tobacco–rice rotation systems of southern China - Bianhong Zhang; Rikun Li; Zhicheng Chen; Chunli Zeng; Songquan Liao; Yazhou Liu; Ting Cheng; Yifei Liu; Lina Tang; Wenxiong Lin; Jinwen Huang (Agriculture, Ecosystems & Environment, 2026)

Health impact assessment of occupational exposure to PM2.5 during welding operations - Siying Liu; Xin Wang; Ziyu Guo; Siyuan Yang; Qiang Zeng; Penghui Li; Ting Wang (Journal of Hazardous Materials, 2026)

Expanded species diversity of fungi in metalliferous mine tailings ponds and their potential ecological roles revealed by PacBio sequencing - Yanying Li; Ting Huang; Weihang Zeng; Rongzhou Jin; Ye Wu; Zhipeng Chen; Qijie Cheng; Xinlin Yu; Xiao-lin Luo; Guan-xiong Wu; Jia-wei Li; Pu Jia; et al. (Journal of Hazardous Materials, 2026)

Byakangelicol Alleviates Ischemic Brain Injury by Inhibiting Microglial Activation and Oxidative Stress - Xiao Wan Wang; Yan Qiong Fu; Zhuo Li Li; Ting Li; Hui Lan Wang; Yu Zheng; Chan Zhang; Miaolin Zeng; Chan Li; Dewei Xie; Bai Hui Chen (Molecular Neurobiology, 2026)

Synergistic control of antibiotic resistance via natural illite-activated peroxymonosulfate: Efficiency and mechanism - Xiangqin Zhou; Ting Zhou; Jiuqiang Xiong; Wenjun Wang; Yingbin Li; Long Li; Xiang Tang; Zhuotong Zeng; Biao Song; Chengyun Zhou; Jing Tong (Journal of Hazardous Materials, 2025)

Metal-center boosted adsorption capacity of bimetallic CeBi-metal organic frameworks for electrochemical monitoring of heavy metal ions in environment and food samples - Huimin Ma; Renhui Yang; Zixuan Xu; Quan Yang; Xiaoxian Hu; Yuanyuan Zhang; Ting Zeng; Juan Yang; Caoling Li; Nianjun Yang (Food Chemistry, 2025)

Human milk fat Substitutes alleviate dextran sulfate sodium induced cognitive deficits in mice by modulating brain fatty acid and ether Lipid metabolism - Yangzheng He; Linhui Zeng; Han Liao; Jing Li; Yong Sun; Hongyan Li; Ting Luo; Zeyuan Deng (Food Bioscience, 2025)

Efficient lithium extraction from salt lakes brine via regulating the electric double-layer interface of high-loading film electrodes with CMC Li - Yawen Gao; Luxiang Ma; Xin Zeng; Zhixiang Li; Ting Li; Chunxi Hai; Tiandong Chen; Yanxia Sun; Shengde Dong; Xin He; Qi Xu; Xiaowang Wu; et al. (Desalination, 2025)

Different Chemical Fertilization Levels Affect Arbuscular Mycorrhizal Fungal Communities in Rhizosphere Soils of Ratoon Sugarcane - Xiao-Juan Qin; Sheng Wang; Ying-Jie Nong; Yi-Hao Kang; Jin-Lian Zhang; Shi-Yuan Zeng; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2025)

Domain Adaptation with Deep Feature Clustering for Pseudo-Label Denoising in Heterogeneous SAR Image Classification - Sheng-Jie Luo; Zhi-Gang Liu; Xi-Hai Li; Yi-Ting Wang; Xiao-Niu Zeng; Zhi-Hao Zheng; Heng Li (Applied Geophysics, 2025)

Discovery of ca. 2.33–2.22 Ga magmatic activities in the Longshan Complex bordering the southwestern margin of the North China Craton: Implications for tectonic transformation - Yi-Yi Zhang; Jun-Sheng Lu; Rui-Ying Zhang; Yu-Ting Li; Xu Kong; Gang Liu; Qiang Feng; Zeng-Yin Duan; Juan-Juan Li (Lithos, 2025)

Nanostructure-enhanced Raman spectroscopy for sensitive and on-site monitoring of anabolic-androgenic steroids in food and drug products - Na Zhou; Yu Zeng; Ting Li; Qiuwen Huang; Yushi Chen; Siqing Liu; Xiaojun Luo; Xiaojun Deng (Food Chemistry, 2025)

Synergistic adsorption and photocatalytic degradation of tetracycline by a functionalized Fe3O4/CuWO4/biochar Z-scheme composite - Dechao Wu; Mengzhu Jiang; Ting Li; Kuan Peng; Yonghong Wang; Yaohui Wu; Yelin Zeng (Environmental Research, 2025)

High-efficient tetracycline removal triggered by Fe-based metal organic framework and sequential reutilization of spent adsorbent - Ting Chang; Yuchen Shang; Shiwen Li; Min Zeng; Jue Liu (Colloids and Surfaces C: Environmental Aspects, 2025)

Intercropping sunflower with amaranth to remediate cadmium-contaminated agricultural land: performance and mechanism - Zhuo-hui Wu; Feifan Wang; Mai Ye; Jingru Zhang; Zhiyi Li; Yunrong Xi; Rongzhou Jin; Yanying Li; Zhipeng Chen; Ye Wu; Ting Huang; Qijie Cheng; et al. (Plant and Soil, 2025)

Comparative transcriptomics unveils nitric oxide delaying leaf senescence in Chinese flowering cabbage by enhancing BrGATA21-mediated ROS scavenging - Zhen-liang Mou; Ze-xiang Zeng; Zong-li Liu; Wei Wei; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen; Ya-ting Zhao (Postharvest Biology and Technology, 2025)

Discovery of a new 1-monoglyceride from Streptomyces albogriseolus JM128 symbiotic with Lendenfeldia sponge - Yun-Ting Zeng; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; You-Ying Chen; Li-Guo Zheng; Chih-Yin Huang; Hsi-Wen Sun; Ping-Jyun Sung (Phytochemistry Letters, 2025)

Heteroaggregation between polystyrene micro(nano)plastics and dibutyl phthalate mediates toxicity reduction in macroalgae: Physiological and transcriptomic evidence from Gracilariopsis lemaneiformis - Yuanxia Li; Xiaoqian Zhang; Nianjun Xu; Mingze Chen; Wenting Tang; Na Zhou; Ting Zeng; Xue Sun; Zeming Zhang (Journal of Hazardous Materials, 2025)

Effect of low-energy stirring temperature on the formation of oil-in-water emulsions stabilized by gelatin-arginine complexes - Jun Qi; Yu-cong Li; Hui-min Yan; Li-ting Zeng; Ao-jing Lv; Rui-ling Dong; Xue-qing Li; Zhou Lin; Le-le Shao; Lang Zhang; Guo-qing Duan; Chun-hui Zhang; et al. (Food Research International, 2025)

Resolving the Genetic Divergence and Population Structure in the Circumpolar Ophiuroid Ophiura sarsii Complex - Yi‐Xuan Li; Sophia Nazarova; Jack Chi‐Ho Ip; Evgeny Genelt‐Yanovskiy; Ting Xu; Yue Dong; Jian‐Wen Qiu; Xue‐Lei Zhang; Qin‐Zeng Xu (Journal of Biogeography, 2025)
Aim The presence of cryptic species causes significant challenges to biodiversity assessment and biological resources management. Here, we investigate the genetic structure and biogeographical patterns of a complex ophiuroid species as a case study. Location Yellow Sea and Funka Bay in the Western Pacific Ocean, Bering Sea in the Arctic Ocean and Barents Sea in the Atlantic Ocean. Taxon The circumpolar ophiuroid Ophiura sarsi i , a common benthic species across the Arctic seas, has at least two cryptic lineages. Methods To better understand the genetic structures and the underlying evolutionary processes in the O. sarsii species complex, we compared the genome‐wide single nucleotide polymorphism (SNP) data and COI of five geographical populations across the northern Pacific, Arctic and Atlantic Oceans using the 2b‐RAD sequencing approach. Results Results clearly showed three highly diverged evolutionary lineages: northern Pacific lineage ( O. sarsii vadicola ), Pacific‐Arctic lineage ( L A ) and Atlantic lineage ( L B ). The divMigrate analysis revealed significant gene flow within O. sarsii vadicola populations and O. sarsii L A populations, but no cross‐species gene flow. Demographic analysis was used to estimate their historical divergence, in which the differentiation of O. sarsii vadicola predated that of the other two lineages of O. sarsii . Molecular dating resulted in an estimation of their divergence events between 3.88 and 1.67 Ma at Pliocene–Pleistocene using COI . Functional analysis revealed several enriched signalling pathways, potentially involved in ophiuroids' environmental adaptation. Main Conclusions Our study suggests three lineages of the cryptic species O. sarsii could split into at least two genetic species, including O. sarsii vadicola , North Pacific–Arctic and Atlantic O. sarsii . The hidden evolutionary trajectory is uncovered for the O. sarsii complex, shaped by paleoclimate and ocean currents. We emphasise the need for genome‐wide SNP applications to understand the ophiuroid biodiversity and contribute to conservation in the Pacific–Arctic region.

KC1036, a multi-kinase inhibitor with anti-angiogenic activity, can effectively suppress the tumor growth of Ewing sarcoma - Xuejin Ou; Ge Gao; Qizhi Ma; Diyuan Qin; Kai Li; Mingyang Feng; Yu Gao; Yao Zeng; Yue Chen; Xia He; Ting Zhang; Zeming Mo; et al. (Angiogenesis, 2025)

How to improve enterprises’ responsiveness to green policies? Empirical evidence from multivariate policy scenario analysis - Liping Wang; Longjun Chen; Ting Zeng; Chuang Li (Environment, Development and Sustainability, 2025)

CCP domain containing protein from complement factor H of Paralichthys olivaceus has potential effects against Edwardsiella piscicida infection - Xuan-yue Wang; Yu-ting Du; Xin-yi Jiang; Zhuo-ran Ma; Chao-ran Zhang; Xue-peng Li; Zeng-zhi Yuan; Mo-fei Li (Aquaculture, 2025)

Petrological and thermodynamic constraints on carbonate stability in altered oceanic crust subducted to subarc depths: Insights from carbonate-bearing eclogites in the Western Alps - Zeng-Li Guo; Jin-Xue Du; Li-Fei Zhang; Thomas Bader; Ren-Biao Tao; Ze-Ming Zhang; Kurt Bucher; Ting-Nan Gong; Jin-Hong Yu (Geochimica et Cosmochimica Acta, 2025)

Efficiency of microbial fermentation on microbial shifts, enzymatic activity, and transcriptions in black soldier fly larvae during the sugarcane waste conversion - Fareed Uddin Memon; ChiHo Li; Sheraz Ahmad; Ying Cui; Xingbao Feng; Peng Zeng; Farhan Nabi; Zhijun Huang; Gianluca Tettamanti; Ting Chen; Ling Tian (Environmental Pollution, 2025)

Associations of phthalate metabolites in urine and follicular fluid with endometrial thickness in the TREE cohort - Xiu-Ting Li; Chong Liu; Yan-Ling Deng; Yu Miao; Min Zhang; Jia-Yue Zeng; Peng-Hui Liu; A.-Xue Liu; Yang-Juan Li; Jin-Qin Zhu; Ning Zhang; Juan Li; et al. (Environmental Toxicology and Pharmacology, 2025)

Calcium salt anion toxicity: Cl- and NO3- differently inhibit Ceratostigma willmottianum photosynthesis - Cailei Liu; Xuan Liu; Qinxiao Zeng; Ting Lei; Long Guo; Jiani Li; Lijuan Yang; Qibing Chen; Suping Gao (Plant and Soil, 2025)

Andrograpalides A–N, structurally diverse ent-labdane diterpenoids with anti-inflammatory activities from the leaves of Andrographis paniculata - Xiao Zhang; Yan-Zhen Li; Ya-Ting Lai; Wei Zeng; Min Yu; Jun-Tao Huang; Hong-Lei Jin; Wei-Qun Yang; Zhong-Xiang Zhao (Phytochemistry, 2025)

Goat milk oligosaccharides improve growth and gut microbiota composition in stunted mice - Xinzhang Chen; Xiaoling Zeng; Fangqin Xiang; Jing Li; Wei Li; Ting Cao; Haixia Wang; Bailiang Li; Jiaqi Wang (Food Research International, 2025)

Nuclear magnetic resonance-based metabolomic study of rat brain after different intensity treadmill running - Ni Zeng; Jie-Ting Li; Zhi-Juan Zhang; Zhi-Peng Yan; Tao Liao; Guo-Xin Ni (Journal of Physiology and Biochemistry, 2025)
Previous studies have revealed that different intensities of exercise training have an impact on cognition. However, the cognitive effects of different intensities of exercise and its underlying mechanisms are not fully understood. The aim of this paper was to investigate the effects of different intensities of treadmill exercise on cognition in rats from the perspective of metabolomic analysis. In this study, ninety-six male rats were randomly divided into four groups: control group (CON group, n = 24), low-intensity running group (LIR group, n = 24), medium-intensity running group (MIR group, n = 24), and high-intensity running group (HIR group, n = 24). After 4 weeks of treadmill running, rats in the LIR group located the platform significantly faster than those in the CON( p = 0.027) and HIR( p = 0.011) groups. After 8 weeks of treadmill running, rats in the LIR and MIR groups also found the platform more quickly than those in CON group ( p = 0.003 and p = 0.015, respectively). Additionally, rats in the MIR group showed significantly increased superoxide dismutase (SOD)/catalase (CAT) in the hippocampus compared with those exposed to HIR( p = 0.03), LIR( p = 0.0008), and CON( p = 0.0004). Metabolomic analysis revealed that, after 8 weeks of running, 14 metabolites with similar characteristics differed between the MIR and HIR groups compared to the CON group. The LIR group showed significant alterations in 12 key metabolites compared to the CON group. The LIR, MIR, and HIR groups also demonstrated significant changes in 3, 4, and 3 metabolic pathways respectively, when compared to the CON group. In conclusion, the above results indicate that LIR can effectively decrease fumarate accumulation, thereby enhancing the TCA cycle and brain energy metabolism which in turn improved cognitive function, while MIR can modify glutathione metabolism to alleviate oxidative stress (OS), supporting cognitive function.

Assessing sensitivity and uncertainty in rod ejection accidents: A combined PCE-POD approach - Yijun Zhang; Wenhuai Li; Sitao Peng; Jinggang Li; Ting Wang; Qingyun He; Tao Wang; Haoliang Lu; Zeng ling (Annals of Nuclear Energy, 2025)

Mechanistic insights into endometriosis: roles of Streptococcus agalactiae and L-carnitine in lesion development and angiogenesis - Yuan Zhuang; Ting Lyu; Yang Chen; Wei Li; Lei Tang; Shi-ping Xian; Peng-fei Yang; Lijie Wang; Qian-qian Zhang; Chaoming Mei; Yu-jing Lin; Zhixiang Yan; et al. (Angiogenesis, 2025)

Delineation of polymetamorphism from the middle-low-grade metamorphic complex in the Dengfeng area, southern North China Craton, resolved by multiple mineral petrochronology and phase equilibrium modelling - Qiang Feng; Jun-Sheng Lu; Xu Kong; Gang Liu; Yu-Ting Li; Yi-Yi Zhang; Zeng-Yin Duan; Juan-Juan Li (Precambrian Research, 2025)

Effects of early-life F-53B exposure on thyroid function in juvenile rats: The role of the cAMP signaling pathway - Shen-Pan Li; Wen-Hui Zhao; Jing Zhang; Wen-Ting Jiang; Jia-Yi Zhu; Yi-Xin Luo; Ping Xiang; Michael Bloom; Pasi Jalava; Guang-Hui Dong; Xiao-Wen Zeng (Journal of Hazardous Materials, 2025)

Arginine-terminated egg white peptide Leu-Phe-Arg (LFR) repairs intestinal barrier damage through the PI3K/AKT/mTOR/p70s6k signaling pathway: An analysis combined transcriptomics and proteomics - Siwen Lyu; Menghan Fu; Qi Yang; Qingwen Han; Shengrao Li; Yingnan Zeng; Jingbo Liu; Yiding Yu; Ting Zhang (Food Bioscience, 2025)

Light intensity is a crucial factor that regulates growth, physiological traits, antioxidant defense, and metabolite acquisition in Dendrobium denneanum - Hui Wang; Siyu He; Yijun Fan; Ting Li; Linlong Xu; Jie Ma; Junlan Wu; Haolin Liu; XuYang Liu; ChunHong Mou; Meng Zhao; Li Chen; et al. (Physiology and Molecular Biology of Plants, 2025)

LncRNA TDRG1 facilitates high glucose–induced retinal microvascular endothelial cell injury via miR-7-5p/G3BP2 - Shuying Xie; Zehong Liu; Ting Luo; Yifa Chen; Liqun Zeng; Xiaoyan Li (In Vitro Cellular & Developmental Biology - Animal, 2025)

Arsenic Accumulation in Different Parent Materials of Rice (Oryza Sative L.) are Affected by Root Morphology - Yi Chen; Dehui Tu; Deqiang Li; Yinggang Xu; Yueyi Wu; Zhaoyong Zeng; Xiaoyan Tang; Yang Li; Chaorui Yan; Ting Lan; Fu Huang; Xuesong Gao; et al. (Journal of Plant Growth Regulation, 2025)

The research on the synergistic improvement of water retention capacity and eating quality of marinated pork meat by the combination of basic arginine and acidic aspartic acid - Kuo Xu; Ao-Jing Lv; Rui-Ling Dong; Yu-Cong Li; Li-Ting Zeng; Yang Wang; He-Shuai Li; Jun Qi; Hu-Hu Wang; Chun-Hui Zhang; Guo-Yuan Xiong; Qing-Yong Zhang (Food Chemistry, 2025)

Modeling diabetic cardiomyopathy using human cardiac organoids: Effects of high glucose and lipid conditions - Xiangyu Wang; Xin Tan; Ting Zhang; Shuai Xu; Yiyao Zeng; Anchen Xu; Xian Li; Ge Zhang; Yufeng Jiang; Hezi Jiang; Jili Fan; Xiaohong Bo; et al. (Chemico-Biological Interactions, 2025)

Knockdown of SMYD3 by RNA Interference Regulates the Expression of Autophagy-Related Proteins and Inhibits Bone Formation in Fluoride-Exposed Osteoblasts - Jie Deng; Xiaoxiao Zeng; Kailin Zhang; Ting Zhang; Yangting Dong; Jian Zou; Changxue Wu; Yi Li; Fucheng Li; Zhizhong Guan (Biological Trace Element Research, 2025)

Luteolin ameliorates ischemic/reperfusion injury by inhibiting ferroptosis - Hua Li; Jin-xia Li; Yi-di Zeng; Cai-xing Zheng; Si-si Dai; Jian Yi; Xu-dong Song; Ting Liu; Wang-hua Liu (Metabolic Brain Disease, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Incorporating Genetic Diversity to Optimize the Plant Conservation Network in the Third Pole - Moses C. Wambulwa; Guang‐Fu Zhu; Ya‐Huang Luo; Zeng‐Yuan Wu; Jim Provan; Marc W. Cadotte; Alistair S. Jump; Francis N. Wachira; Lian‐Ming Gao; Ting‐Shuang Yi; Jie Cai; Hong Wang; et al. (Global Change Biology, 2025)
Climate change poses a significant threat to the survival of many species. Although protected areas can slow down biodiversity loss, they often lack systematic planning and do not integrate genetic diversity. Genetic diversity is a key prerequisite for species survival and the ability to tolerate new conditions. Using population genetic and distribution data from 96 plant species in the Third Pole (encompassing the Tibetan Plateau and adjacent mountains), we mapped patterns of genetic diversity, projected climate‐driven range dynamics and future genetic erosion, and designed an optimal conservation framework for the region. We identified several patches of high haplotype diversity ( H D ), with a relatively high number of haplotypes in southeastern Third Pole. Regression models revealed that climate and topography have interacted to shape patterns of genetic diversity, with latitude and precipitation being the best predictors for H D of cpDNA and nrDNA, respectively. Ecological niche modeling predicted an approximate 43 km northwestward and 86 m upward shift in suitable habitats under future climate scenarios, likely leading to a significant loss of up to 13.19% and 15.49% of cpDNA and nrDNA genetic diversity, respectively. Alarmingly, 71.20% of the newly identified conservation priority areas fall outside of the existing protected areas and planned National Park Clusters. Therefore, we recommend expanding the network by 2.02 × 10 5 km 2 (5.91%) in the Third Pole, increasing the total conserved area to 1.36 × 10 6 km 2 (39.93%) to effectively preserve the evolutionary potential of plants. This study represents an innovative attempt to incorporate genetic diversity into biodiversity conservation efforts.

Argonaute 1 negatively regulates cadmium tolerance via modulating jasmonic acid and gibberellin contents, antioxidant enzymes, and chlorophyll level in tobacco - Ting Yang; Xinyu Zhang; Hui Zhang; Xingpeng Jiang; Xu Yuan; Weida Chen; Jianan Li; Changli Zeng (Journal of Hazardous Materials, 2025)

The miR172a–SNB module orchestrates both induced and adult-plant resistance to multiple diseases via MYB30-mediated lignin accumulation in rice - He Wang; Zhe-Xu Wang; Hong-Yuan Tian; Yu-Long Zeng; Hao Xue; Wan-Ting Mao; Lu-Yue Zhang; Jun-Ni Chen; Xiang Lu; Yong Zhu; Guo-Bang Li; Zhi-Xue Zhao; et al. (Molecular Plant, 2025)

Effects of cloprostenol and oxytocin on ultrasonographic changes of uterine horns in postpartum primiparous Hu sheep - Yixuan Li; Zongling Liu; Wenqian Zhang; Chunhao Zhu; Xi Chen; Yukun Zhao; Lei Liu; Ting Ting Zhu; Mingyang Geng; Yanping Wang; Weibin Zeng (Animal Reproduction Science, 2025)

Potential health risk of human exposure to tobacco-specific nitrosamines in second-hand and third-hand smoke - Si-Qi Wang; Lian-Jun Bao; Ting-Yu Li; Eddy Y. Zeng (Journal of Hazardous Materials, 2024)

Potential of Salvinia biloba Raddi for the remediation of water polluted with ciprofloxacin: Removal, physiological response, and root microbial community - Zhangxiong Luo; Meng Qin; Zicong Guo; Xuxin Li; Ting Zhou; Zhuotong Zeng; Chengyun Zhou; Biao Song (Journal of Hazardous Materials, 2024)

The preparation of fish scale gelatin-polydopamine photothermal sterilization film and its application for storage of cherry tomato - Yunfeng Yang; Xiulian Li; Ting Zhang; Xiangquan Zeng; Fengjun Guo; Quanwen Liu; Xinguang Fan; Da-Peng Yang (Food Packaging and Shelf Life, 2024)

Free-standing, robust, hyperconnective hybrid nanofiber nonwovens enabled by interpenetrating network for oily aerosols purification - Weitao Zhou; Yiming Li; Zeng Qu; Sen Li; Ting Wu; Jingliang Li; Tingting Shi; Jikai Chen; Boyu Li; Haitao Huang; Shan Du (Chemical Engineering Journal, 2024)

Hg-mining-induced soil pollution by potentially toxic metal(loid)s presents a potential environmental risk and threat to human health: A global meta-analysis - Li Chen; Xiaosan Luo; Haoran He; Ting Duan; Ying Zhou; Lequn Yang; Yi Zeng; Hansong Chen; Linchuan Fang (Soil Ecology Letters, 2024)

Unraveling the toxicity mechanisms of nanoplastics with various surface modifications on Skeletonema costatum: Cellular and molecular perspectives - Ting-Ting Xu; Zhen-Liang Li; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Tao Li; Eddy Y. Zeng; Ke-Fu Yu; Xiang-Rong Xu (Science of The Total Environment, 2024)

High emission of black carbon in heavy-duty diesel vehicles: Insights from microscopic operating conditions - Ting Chen; Xiao He; Liqiang He; Yan You; Lewei Zeng; Mingqiu Gao; Fengbin Wang; Yihuan Cao; Zhenhua Li; Xuan Zheng; Shaojun Zhang; Guangyi Xu; et al. (Science of The Total Environment, 2024)

Accumulation and metabolism of selenium in the rare yeast Kazachstania unispora during the selenium enrichment process - Furong Wang; Xiaoben Li; Xian Wang; Ivan Kurtovic; Min Yan; Jianping Wei; Ting Zhang; Xuejun Zeng; Yahong Yuan; Tianli Yue (Food Chemistry, 2024)

Intrauterine exposure to long-chain perfluorocarboxylic acids (PFCAs) were associated with reduced primary bile acids in three-year-old children: Findings from a prospective birth cohort study - Yu-Ting Guo; Jin-bo Huang; Jing-chuan Xue; Shuang-Jian Qin; Dan Cai; Qi-Zhen Wu; Chu Chu; Cui-lan Tang; Yan-qi Xie; Li-Zi Lin; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2024)

Combined Remediation Effects of Sewage Sludge and Phosphate Fertilizer on Pb-Polluted Soil from a Pb-Acid Battery Plant - Ting Zhang; Xiong Yang; Zhijia Zeng; Qiang Li; Jiahai Yu; Huiling Deng; Yafei Shi; Huiqin Zhang; Andrea R. Gerson; Kewu Pi (Environmental Management, 2024)

Sirt4 Overexpression Modulates the JAK2/STAT3 and PI3K/AKT/mTOR Axes to Alleviate Sepsis-Induced Acute Lung Injury - Cancan Xie; Ting Wang; Anmin Liu; Bing Huang; Weizhong Zeng; Zhengrong Li; Suna Peng; Shuanghua Wu (Cell Biochemistry and Biophysics, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Spatially lipidomic characterization of patient-derived organoids by whole-mount autofocusing SMALDI mass spectrometry imaging - Chunyan Lan; Ying Peng; Hengtong Zuo; Jianying Pei; Yue Li; Ting Zhang; Hainan Wu; Liyuan Du; Chang Zeng; Hongmei Zhao; Xiaofang Chen; Huafang Gao (Analytica Chimica Acta, 2024)

Preparation of gelatin-starch shell-yolk microspheres by water-in-water emulsion method: Effects of starch crystal type and cross-linking - Zhirenyong Zhang; Xiaoxue He; Ting Yan; Yuyu He; Chaoxi Zeng; Shiyin Guo; Qingming Li; Huiping Xia (Food Hydrocolloids, 2024)

Research on heat dissipation optimization and energy conservation of supercapacitor energy storage tram - Yibo Deng; Sheng Zeng; Chushan Li; Ting Chen; Yan Deng (Waste Disposal & Sustainable Energy, 2024)

Overexpression of the MiAGL1 gene from mango promoted flowering in transgenic Arabidopsis - Xue-mei Zeng; Xin-hua He; Wen-jing Mo; Hai-xia Yu; Ting-ting Lu; Li-ming Xia; Yi-li Zhang; Jia-wei Zhu; Cong Luo (Journal of Plant Biochemistry and Biotechnology, 2024)

Evaluation of a new real-time source apportionment system of PM2.5 and its implication on rapid aging of vehicle exhaust - Pei-Ting Yao; Xing Peng; Li-Ming Cao; Li-Wu Zeng; Ning Feng; Ling-Yan He; Xiao-Feng Huang (Science of The Total Environment, 2024)

Natural aromatic extract of black tea improved the water retention of pork meat batter - Wen-ping Xu; Rui-ling Dong; Ao-jing Lv; Yu-cong Li; Li-ting Zeng; Xue-ling Gao; Jun Qi; Zhou Lin; Hui-min Yan; Chun-hui Zhang; Guo-yuan Xiong (Food Research International, 2024)

Teleost-specific TLR23 in Takifugu rubripes recruits MyD88 to trigger ERK pathway and promotes antibacterial defense - Yu-ting Du; Hong-qiang Zhang; Yan Li; Xue-peng Li; Zeng-zhi Yuan; Mo-fei Li (Fish & Shellfish Immunology, 2024)

Occurrence and mechanism of sulfamethoxazole in alginate-like extracellular polymers from excess sludge - Chen Shi; Ming Cheng; Run-Gen Zeng; Cong-Cong Li; Qian Wang; Li-Ting Hao; Ran-Bin Liu; Xiao-Di Hao; Xiang-Yang Wang; Yuan-Yuan Wu (Bioresource Technology, 2024)

Viscoelastic cues to induce stem cell migration and neuronal differentiation in cell-free hydrogel-assisted TBI recovery - Xiaoyin Liu; Chengheng Wu; Yusheng Zhang; Gaowei Li; Suping Chen; Zhihong Chen; Peng Liu; Kai Wu; Xiaoyang Wu; Ting Zhou; Mingze Zeng; Zi Qiao; et al. (Chemical Engineering Journal, 2024)

Triclocarban and triclosan promote breast cancer progression in vitro and in vivo via activating G protein-coupled estrogen receptor signaling pathways - Ting-Ting He; Xin Li; Jie-Zhi Ma; Yuan Yang; Shiye Zhu; Jianhua Zeng; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2024)

Exposure to per- and polyfluoroalkyl substances in lung cancer patients and their associations with clinical health indicators - Si-Nan Huang; Ying-Hua Hu; Ting-Ting Xu; Yu-Ling Luan; Li-Xi Zeng; Zi-Feng Zhang; Ying Guo (Environmental Pollution, 2024)

A Combined Manual Annotation and Deep-Learning Natural Language Processing Study on Accurate Entity Extraction in Hereditary Disease Related Biomedical Literature - Dao-Ling Huang; Quanlei Zeng; Yun Xiong; Shuixia Liu; Chaoqun Pang; Menglei Xia; Ting Fang; Yanli Ma; Cuicui Qiang; Yi Zhang; Yu Zhang; Hong Li; et al. (Interdisciplinary Sciences: Computational Life Sciences, 2024)
We report a combined manual annotation and deep-learning natural language processing study to make accurate entity extraction in hereditary disease related biomedical literature. A total of 400 full articles were manually annotated based on published guidelines by experienced genetic interpreters at Beijing Genomics Institute (BGI). The performance of our manual annotations was assessed by comparing our re-annotated results with those publicly available. The overall Jaccard index was calculated to be 0.866 for the four entity types—gene, variant, disease and species. Both a BERT-based large name entity recognition (NER) model and a DistilBERT-based simplified NER model were trained, validated and tested, respectively. Due to the limited manually annotated corpus, Such NER models were fine-tuned with two phases. The F1-scores of BERT-based NER for gene, variant, disease and species are 97.28%, 93.52%, 92.54% and 95.76%, respectively, while those of DistilBERT-based NER are 95.14%, 86.26%, 91.37% and 89.92%, respectively. Most importantly, the entity type of variant has been extracted by a large language model for the first time and a comparable F1-score with the state-of-the-art variant extraction model tmVar has been achieved. Graphical Abstract

Soil physicochemical properties and plant functional traits regulate ecosystem multifunctionality of alpine grassland under different livestock grazing assemblies - Bin Feng; Yu-Zhen Liu; Wen-Ting Liu; Wei-Dong Lv; Cai-Cai Sun; Zeng-Zeng Yang; Cai-Di Li; Qin-Yuan Zhou; Fang-Cao Wang; Xiao-Xia Yang; Quan-Min Dong (Agriculture, Ecosystems & Environment, 2024)

Coastal hypoxia response to the coupling of catastrophic flood, extreme marine heatwave and typhoon: a case study off the Changjiang River Estuary in summer 2020 - Xiao Ma; Qicheng Meng; Dewang Li; Yuanli Zhu; Xiaobo Ni; Dingyong Zeng; Di Tian; Ting Huang; Zhihao Jiang; Haiyan Jin; Feng Zhou (Acta Oceanologica Sinica, 2024)

Aconitum coreanum and processed products on its base prevent stroke via the PI3K/Akt and KEAP1/NRF2 in the in vivo study - Wan-ting Zeng; Li-ting Zhou; Ru Jia; Yue Liu; Qian Cai; Yang Qu (Metabolic Brain Disease, 2024)

Two new monoterpene esters from Illigera paviflora Dunn roots - Meng-Yuan Jiang; Xiao-Yun Pu; Wen-Ting Li; Juan Liu; Xiao-Li Zeng; Hong-Rui Li; Xi-Shan Bai; Lin Hu; Xiang-Zhong Huang (Natural Product Research, 2024)

Preparing a heavy-metal adsorbent based on alginate-like extracellular polymers from conventional activated sludge via polyethyleneimine grafting - Chen Shi; Run-Gen Zeng; Shi-Chao Yuan; Lin Zhang; Xiang-Yang Wang; Li-Ting Hao; Xiao-Di Hao; Nan Zhang; Yuan-Yuan Wu (Sustainable Chemistry and Pharmacy, 2024)

Toxicological evaluation and concentration of airborne PM0.1 in high air pollution period in Guangzhou, China - Mo Yang; Qi-Zhen Wu; Yun-Ting Zhang; Ari Leskinen; Xin-Feng Wang; Mika Komppula; Henri Hakkarainen; Marjut Roponen; Nan-Xiang Jin; Wei-Hong Tan; Shu-Li Xu; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Citrus transcription factor CsERF098 cooperates with CsWRKY70 to participate in response of fruit to green mold - Ting Li; Wenjun Wang; Qi Chen; Ou Chen; Linli Wei; Lili Deng; Shixiang Yao; Kaifang Zeng (Postharvest Biology and Technology, 2024)

Methyl jasmonate regulation of pectin polysaccharides in Cosmos bipinnatus roots: A mechanistic insight into alleviating cadmium toxicity - Chun-Yu Fan; Xiao-Fang Yu; Yu-Jia Liu; Xiao-Xuan Zeng; Fu-Wen Luo; Xian-Tong Wang; Xuan Yang; Xiao-Yu Wang; Xiao Xue; Li-Juan Yang; Ting Lei; Ming-Yan Jiang; et al. (Environmental Pollution, 2024)

Research progress of the effects of bisphenol analogues on the intestine and its underlying mechanisms: A review - Min Zhu; Ran Zeng; Dan Wu; Yuanyuan Li; Ting Chen; Aijie Wang (Environmental Research, 2024)

Complete decomposition of poly(ethylene terephthalate) by crude PET hydrolytic enzyme produced in Pichia pastoris - Chun-Chi Chen; Xian Li; Jian Min; Ziyin Zeng; Zhiyuan Ning; Hailin He; Xin Long; Du Niu; Rouming Peng; Xin Liu; Yu Yang; Jian-Wen Huang; et al. (Chemical Engineering Journal, 2024)

Prenatal exposures to phthalates and bisphenols in relation to oxidative stress: single pollutant and mixtures analyses - Jia-Yue Zeng; Min Zhang; Xu-Hui Chen; Chong Liu; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Tian Shi; Ting-Ting Lu; Xiao-Ying Liu; Yang Wu; et al. (Environmental Science and Pollution Research, 2024)

Do natural resources ensure energy efficiency? A novel paradigm of resources-efficiency nexus for sustainable development - Queling Zeng; Ruida Li; Ting Zhang (Resources Policy, 2023)

Seroprevalence and potential risk factors of brucellosis in sheep from America, Africa and Asia regions: A systematic review and meta-analysis - Lian-Min Li; Qi Wang; Jun-Feng Shi; Ting Li; Bo Zhao; Qing-Xia Ma; Hong-Ying Liu; Nuo Su; Ruo-Peng Cai; Fan-Li Zeng; Qing-Long Gong; Kun Shi; et al. (Research in Veterinary Science, 2023)

A review of alginate-like extracellular polymers from excess sludge: Extraction, characterization, and potential application - Run-Gen Zeng; Chen Shi; Li-Ting Hao; Ao Huang; Tian Yuan; Nan Zhang (Journal of Water Process Engineering, 2023)

17β-Estradiol Mediates Staphylococcus aureus Adhesion in Vaginal Epithelial Cells via Estrogen Receptor α-Associated Signaling Pathway - Lina Yan; Can Rui; Bin Zhuang; Xia Liu; Ting Luan; Lisha Jiang; Zhiyong Dong; Qing Wang; Aiwen Wu; Ping Li; Xinyan Wang; Xin Zeng (Current Microbiology, 2023)

Human dental pulp stem cells have comparable abilities to umbilical cord mesenchymal stem/stromal cells in regulating inflammation and ameliorating hepatic fibrosis - Peixing Chen; Yanchun Lin; Wenbo Lin; Yun Li; Ting Fu; Yuanyue Liu; Tian Guan; Man Xin; Ling Ye; Peiluan Wang; Haoyu Zeng; Kaitao Yao (Human Cell, 2023)

Proteomic characteristics of six snake venoms from the Viperidae and Elapidae families in China and their relation to local tissue necrosis - Wan-Gang Qin; Zhan-Peng Zhuo; Hao Hu; Mimi Lay; Qian-Qin Li; Jun-Ting Huang; Liang-Bo Zeng; Zi-Jing Liang; Fei Long; Qing Liang (Toxicon, 2023)

CsAP2L transcription factor regulates resistance of citrus fruit to Penicillium digitatum through lignin biosynthesis and ROS metabolism pathways - Jialin Chen; Wenjun Wang; Ting Li; Xiaoquan Gao; Xuan Zhang; Kaifang Zeng (Postharvest Biology and Technology, 2023)

Sperm quality decline associated with gaseous pollutant exposure: Evidence from a large cohort multicenter study - Xiaoyan Cai; Haobo Ni; Qiling Wang; Tingting Dai; Lingxi Wang; Chunying Song; Yushan Li; Fuping Li; Tianqing Meng; Huiqiang Sheng; Lina Xiao; Ting Xu; et al. (Journal of Hazardous Materials, 2023)

Per- and polyfluoroalkyl substances in ambient fine particulate matter in the Pearl River Delta, China: Levels, distribution and health implications - Lu-Sheng Liu; Yu-Ting Guo; Qi-Zhen Wu; Mohammed Zeeshan; Shuang-Jian Qin; Hui-Xian Zeng; Li-Zi Lin; Wei-Chun Chou; Yun-Jiang Yu; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2023)

Microbiological Characteristics and Risk Factors Involved in Progression from Fungal Keratitis with Hypopyon to Keratitis-Related Endophthalmitis - Yu Sun; Fanxing Zeng; Jingjing Zhang; Xiaolin Qi; Xiuhai Lu; Na Ning; Suxia Li; Ting Zhang; Gongqiang Yuan; Weiyun Shi; Hua Gao (Mycopathologia, 2023)

Soil ridging combined with biochar or calcium-magnesium-phosphorus fertilizer application: Enhanced interaction with Ca, Fe and Mn in new soil habitat reduces uptake of As and Cd in rice - Ting Zhang; Md. Abu Sayem Jiku; Lingyi Li; Yanxin Ren; Lijuan Li; Xibai Zeng; Gilles Colinet; Yuanyuan Sun; Lijuan Huo; Shiming Su (Environmental Pollution, 2023)

Treatment of diluted palm oil mill effluent (POME) synchronous with electricity production in a persulfate oxidant-promoted photocatalytic fuel cell - Chun-Ting Joyee Yap; Sze-Mun Lam; Jin-Chung Sin; Honghu Zeng; Haixiang Li; Liangliang Huang; Hua Lin (Environmental Science and Pollution Research, 2023)

H2S-releasing versatile hydrogel dressing with potent antimicrobial, anti-inflammatory, epithelialization and angiogenic capabilities for diabetic wound healing - Jiale Chen; Zhixiang Mu; Dongfan Chen; Chen Huang; Ting Jin; Lin Li; Youyun Zeng; Qiang Zhou; Yanmei Zhang; Hongli Mao; Hui Deng; Xinkun Shen; et al. (Chemical Engineering Journal, 2023)

Gross nitrogen transformations and ammonia oxidizers affected by nitrification inhibitors and/or organic amendments in a calcareous soil: A 15N tracing study - Xiaoqian He; Mengxiao Li; Minghua Zhou; Wei Zhou; Guangdeng Chen; Yanyan Zhang; Yang Li; Min Zeng; Xuesong Gao; Ting Lan (Applied Soil Ecology, 2023)

Two new diterpenoids from the rhizomes of Zingiber officinale - Mi Zhou; Ting Li; Chen Zeng; Da-bo Pan; Hai-bo Li; Yang Yu (Natural Product Research, 2023)

Transcriptional regulatory mechanism of a variant transcription factor CsWRKY23 in citrus fruit resistance to Penicillium digitatum - Wenjun Wang; Ting Li; Qi Chen; Shixiang Yao; Kaifang Zeng (Food Chemistry, 2023)

Extracellular biomineralization of uranium and its toxicity alleviation to Bacillus thuringiensis X-27 - Ting Zhu; Qian Zeng; Changsong Zhao; Yufeng Wen; Shangqing Li; Feize Li; Tu Lan; Yuanyou Yang; Ning Liu; Qun Sun; Jiali Liao (Journal of Environmental Radioactivity, 2023)

Inducing the structural interplay of binary pulse protein complex to stimulate the solubilization of chickpea (Cicer arietinum L.) protein isolate - Yongxin Teng; Ting Zhang; Hongmin Dai; Yabin Wang; Jianteng Xu; Xin-An Zeng; Bin Li; Xiangwei Zhu (Food Chemistry, 2023)

Extracting compositional blocks of alginate-like extracellular polymers (ALE) from conventional activated sludge (CAS) - Chen Shi; Run-Gen Zeng; Li-Ting Hao; Xiao-Di Hao; Ji Li (Science of The Total Environment, 2023)

A self-regulated transcription factor CsWRKY33 enhances resistance of citrus fruit to Penicillium digitatum - Wenjun Wang; Ting Li; Jialin Chen; Xuan Zhang; Linli Wei; Shixiang Yao; Kaifang Zeng (Postharvest Biology and Technology, 2023)

Transcription factor CsERF1B regulates postharvest citrus fruit resistance to Penicillium digitatum - Ting Li; Wenjun Wang; Qi Chen; Jialin Chen; Xuan Zhang; Linli Wei; Lili Deng; Shixiang Yao; Kaifang Zeng (Postharvest Biology and Technology, 2023)

Complete genome sequence of one novel marine Pseudomonas sp. BSw22131 growing with dimethylsulfoniopropionate (DMSP) as the sole carbon source - Ting Hu; Yin-Xin Zeng; Yi-He Zhang; Yu Du; Wei Han; Hui-Rong Li; Wei Luo (Marine Genomics, 2023)

Preparation and characterization of carboxymethyl chitosan/pullulan composite film incorporated with eugenol and its application in the preservation of chilled meat - Zhen Zeng; Yu-Jing Yang; Qian Tu; Yu-Ying Jian; Da-Ming Xie; Ting Bai; Shan-Shan Li; Yun-Tao Liu; Cheng Li; Cai-Xia Wang; Ai-Ping Liu (Meat Science, 2023)

Environmental fate of microplastics in an urban river: Spatial distribution and seasonal variation - Ting Li; Kai Liu; Rui Tang; Jun-Rong Liang; Lei Mai; Eddy Y. Zeng (Environmental Pollution, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

The Nasal Bacteria Microbiome Comparison Among Fungal Ball Sinusitis, Chronic Sinusitis with Polyps - Pengyu Shi; Hongzheng Wei; Xin Liu; Shouxiang Dong; Shuai He; Yun Zeng; Ting Yang; Chengyao Liu; Yunchuan Li (Indian Journal of Microbiology, 2023)

Effect of chromium stress on metal accumulation and cell wall fractions in Cosmos bipinnatus - XiaoFang Yu; ZiHan Yang; YuHan Xu; ZhiWen Wang; ChunYu Fan; XiaoXuan Zeng; YuJia Liu; Ting Lei; MingYan Jiang; JiaNi Li; Xue Xiao; LiJuan Yang; et al. (Chemosphere, 2023)

Bioleaching and immobilizing of copper and zinc using endophytes coupled with biochar-hydroxyapatite: Bipolar remediation for heavy metals contaminated mining soils - Weiran Feng; Xiao Xiao; Junjie Li; Qicheng Xiao; Li Ma; Qifeng Gao; Yuke Wan; Yutian Huang; Ting Liu; Xubiao Luo; Shenglian Luo; Guisheng Zeng; et al. (Chemosphere, 2023)

The size of the susceptible pool differentiates climate effects on seasonal epidemics of bacillary dysentery - Haobo Ni; Qinghui Zeng; Ting Xu; Lina Xiao; Xiaolin Yu; Jinrui Hu; Yang Li; Hualiang Lin; Pi Guo; Haijian Zhou (Science of The Total Environment, 2023)

Genome-wide identification of the CsPAL gene family and functional analysis for strengthening green mold resistance in citrus fruit - Linli Wei; Wenjun Wang; Ting Li; Ou Chen; Shixiang Yao; Lili Deng; Kaifang Zeng (Postharvest Biology and Technology, 2023)

Intercomparison and evaluation of ten global ET products at site and basin scales - Huiyuan Liu; Xiaozhou Xin; Zhongbo Su; Yijian Zeng; Ting Lian; Li Li; Shanshan Yu; Hailong Zhang (Journal of Hydrology, 2023)

Mo isotopes archive oceanic sediments in post-orogenic lithospheric mantle - Feng Huang; Jie Li; Jifeng Xu; Jianlin Chen; Baodi Wang; Pan Hu; Rong Xu; Yunchuan Zeng; Le Zhang; Ting Zhou (Geochimica et Cosmochimica Acta, 2023)

A thin LiGa alloy layer from in-situ electroreduction to suppress anode dendrite formation in lithium-sulfur pouch cell - Rong Li; Liwen Yang; Lei Song; Changan Zhou; Jiayu Zhou; Ting Chen; Chen Wu; Yujia Zeng; Kui Ma; Hairong Yue (Chemical Engineering Journal, 2023)

The role of ancestral seascape discontinuity and geographical distance in structuring rockfish populations in the Pacific Northwest - Cheng-He Sun; Rodolphe Elie Gozlan; Ting Wu; Dan Xue; Ye-Ling Lao; Jian-Feng Yu; Xiao-Shu Zeng; Sha Li; Emilie A. Hardouin; Demetra Andreou; Qun Zhang (Frontiers in Marine Science, 2022)
Despite the apparent absence of physical barriers in the ocean to prevent dispersal, recent studies have highlighted the importance of biological, geographical, physical, and historical barriers in the genetic structuring of marine species populations. This representation is essential for the sustainable exploitation of natural marine resources and for the setup of efficient protected area networks for the conservation of marine species. In this study, we used extensive sampling of Sebastiscus marmoratus , a commercially important inshore rockfish with high site fidelity, to characterize their population genetic structure along the China–Japan coast and to determine the effect of past geological and current biological–physical barriers on the current genetic footprint. A 461-bp fragment of the mtDNA hypervariable portion control region was sequenced for 675 individuals from 15 geographical locations. A total of 292 haplotypes were identified. The population of S. marmoratus showed high haplotype and nucleotide diversity. Pairwise fixation index ( F ST ) and analysis of molecular variance (AMOVA) revealed significant genetic differentiation among populations. The Bayesian skyline plots and neutrality statistics showed a sudden expansion of the S. marmoratus population around the Pleistocene. The Beibu Gulf group had the lowest mean number of pairwise differences, the lowest significant genetic differentiation, and the lowest haplotype and nucleotide diversity, and should be prioritized for protection in the future. Ocean currents, seascape discontinuity, geographical distance, and ecological characteristics may play an important role in shaping the contemporary phylogeographical patterns and population structures of S. marmoratus .

Characterization and mutagenesis of a novel Mycobacterium smegmatis-derived glutamate decarboxylase active at neutral pH - Yudi Li; Guiying Chen; Fanglan Ge; Ting Dang; Yao Ren; Bei Zeng; Wei Li (World Journal of Microbiology and Biotechnology, 2022)

Effects of synthetic nitrification inhibitor (3,4-dimethylpyrazole phosphate; DMPP) and biological nitrification inhibitor (methyl 3-(4-hydroxyphenyl) propionate; MHPP) on the gross N nitrification rate and ammonia oxidizers in two contrasting soils - Ting Lan; Mengxiao Li; Xiaoqian He; Ouping Deng; Wei Zhou; Ling Luo; Guangdeng Chen; Shu Yuan; Jing Ling; Min Zeng; Xuesong Gao (Biology and Fertility of Soils, 2022)

Preparation and In Vitro and In Vivo Evaluation of a Testosterone Film Forming Gel for the Treatment of Hypoactive Sexual Desire Disorder in Women - Jia Zeng; Tan-Fang Xie; Ting Huang; Fang Li; Zhi-Ping Wang; Ling-Lin Feng (AAPS PharmSciTech, 2022)

Transcriptomic analyses provide insight into adventitious root formation of Euryodendron excelsum H. T. Chang during ex vitro rooting - Yuping Xiong; Shuangyan Chen; Zhenpeng Wei; Xiaohong Chen; Beiyi Guo; Ting Zhang; Yuying Yin; Xincheng Yu; Jinhui Pang; Meiyun Niu; Xinhua Zhang; Yuan Li; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Biological monitoring and health assessment of 21 metal(loid)s in children and adolescents in Liuzhou City, Southwest China - Yaping Li; Yu Zhang; Meng Yu; Liqin Hu; Ting Zeng; Ling Liu; Limei Wang; Liangqiong Deng; Xiang Li; Ping Liu; Dingyuan Zeng; Surong Mei (Environmental Science and Pollution Research, 2022)

Longitudinal associations of sleep duration and sleep quality with coronary heart disease risk among adult population: classical meta-analysis and Bayesian network meta-analysis - Rui Zeng; Yu-ting Jiang; Tian-wu Chen; Dan-dan Guo; Rui Li (Sleep and Biological Rhythms, 2021)

Antifungal Effect of Long Noncoding RNA 9708-1 in the Vulvovaginal Candidiasis Murine Model - Ying Wu; Lisha Jiang; Lingling Zhang; Xia Liu; Lina Yan; Ting Luan; Can Rui; Zhiyuan Mao; Chong Fan; Yu Liu; Ping Li; Xin Zeng (Mycopathologia, 2021)
Vulvovaginal candidiasis (VVC) caused by Candida spp. affects 70–75% of women at least once during their lives. We aim to elucidate the potential mechanism of VVC and investigate the therapeutic effects of long noncoding RNA 9708-1. Female BALB/c mice were randomized to four treatment groups, including the blank control group, VVC control group, vehicle control group and lncRNA 9708-1-overexpressed group. Mice were euthanized on Day 4, Day 7 and Day 14 after treatment. Colony-forming unit (CFU) was measured, and the inflammation was detected by hematoxylin and eosin (H&E). Gene and protein expression levels of lncRNA 9708-1 and FAK were determined by real-time PCR, Western blot and immunohistochemistry. The overexpression of lncRNA 9708-1 significantly decreased the fungal load from Day 4 to 7. H&E staining indicated that the impaired histological profiles were improved in lncRNA 9708-1-overexpressed group. LncRNA 9708-1 led to a significant increase in FAK level of vagina tissue which is expressed mainly in epithelial basal layer. This study suggests that lncRNA 9708-1 played a protective role on murine experimental VVC by upregulating the expression levels of FAK.

Chemical composition of Erycibe schmidtii and antiproliferative activity of scopoletin on immature dendritic cells - Wang Ren; Yantang Wang; Qinhui He; Yue Zhou; Chunxin Li; Wenling Wang; Xiao Leng; Ting Zeng; Qiang Zou; Limei Li (Natural Product Research, 2020)

Chemical characterization of constituents from Polygonatum cyrtonema Hua and their cytotoxic and antioxidant evaluation - Ting Zeng; Yan-Ran Tang; Bin Li; Shumaila Tasneem; Han-Wen Yuan; Yan-Zhe Jia; Muhammad Daniyal; Nusrat Hussain; Wen-Miao Wang; Da-Lei Zuo; Li-Min Gong; Bin Liu; et al. (Natural Product Research, 2020)

Gastrointestinal involvement of COVID-19 and potential faecal transmission of SARS-CoV-2 - Min Song; Zong-lin Li; Ye-jiang Zhou; Gang Tian; Ting Ye; Zhang-rui Zeng; Jian Deng; Hong Wan; Qing Li; Jin-bo Liu (Journal of Zhejiang University-SCIENCE B, 2020)

Chopper Sugarcane Combine Harvester with Middle-Mounted Primary Extractor - Tao Wu; Xiao-Ling Liang; Qing-Ting Liu; Zeng-Xue Zhang; Hai Xu; Ji-Bai Huang; Jin-Xin Li; Xiao-Ping Zou (Sugar Tech, 2020)

Transcriptome Analysis of Two Strains of Proteus mirabilis with Swarming Migration Deficiency Isolated from Patients with Urinary Tract Infection - Liang Peng; Ding-Qiang Chen; Guan-Ming Jiang; Jing-Yi Ou; Qiao Jiang; Li-Ting Zeng; Yi Xiao; Qiong-Yan Jiang; Ling Yang; Ning Sun (Current Microbiology, 2020)

The Role of 17β-Estrogen in Candida albicans Adhesion on Human Vaginal Epithelial Cells via FAK Phosphorylation - Ting Luan; Xia Liu; Pengyuan Mao; Xinyan Wang; Can Rui; Lina Yan; Yiquan Wang; Chong Fan; Ping Li; Xin Zeng (Mycopathologia, 2020)

Characterization of the complete mitochondrial genome of an endangered fish Semilabeo obscurus (Cyprinidae; Labeoninae; Semilabeo) - Wei Wang; Shikai Li; Ting Liu; Xue Wang; Sheng Zeng; Wenwu Min; Lu Zhou (Conservation Genetics Resources, 2019)

Immobilization of heavy metals in two contaminated soils using a modified magnesium silicate stabilizer - Xingzhong Yuan; Ting Xiong; Hou Wang; Zhibin Wu; Longbo Jiang; Guangming Zeng; Yue Li (Environmental Science and Pollution Research, 2018)

A comparison of CRISPR/Cas9 and siRNA-mediated ALDH2 gene silencing in human cell lines - Fei Wang; Tao Guo; Hongmei Jiang; Ruobi Li; Ting Wang; Ni Zeng; Guanghui Dong; Xiaowen Zeng; Daochuan Li; Yongmei Xiao; Qiansheng Hu; Wen Chen; et al. (Molecular Genetics and Genomics, 2018)

Saikosaponin D relieves unpredictable chronic mild stress induced depressive-like behavior in rats: involvement of HPA axis and hippocampal neurogenesis - Hong-Yan Li; Ying-Hua Zhao; Min-Jie Zeng; Fang Fang; Min Li; Ting-Ting Qin; Lu-Yu Ye; Hong-Wei Li; Rong Qu; Shi-Ping Ma (Psychopharmacology, 2017)

A new sucrosephenylpropanoid ester from Polygonum pubescens Blume - Qiang Liu; Bin Li; Jianping Zhao; Shabana I. Khan; Wen-Bin Liu; Ting Zeng; Cai-Yun Peng; Xiong Cai; Qinghua Peng; Huiyong Huang; Ikhlas A. Khan; Wei Wang (Natural Product Research, 2017)

Effects of different ratios of glucose to acetate on phosphorus removal and microbial community of enhanced biological phosphorus removal (EBPR) system - Ting Xie; Chuangrong Mo; Xiaoming Li; Jian Zhang; Hongxue An; Qi Yang; Dongbo Wang; Jianwei Zhao; Yu Zhong; Guangming Zeng (Environmental Science and Pollution Research, 2017)

Influence of genetic polymorphisms in cytochrome P450 oxidoreductase on the variability in stable warfarin maintenance dose in Han Chinese - Wu-Tao Zeng; Qing Xu; Cheng-Hsun Li; Wei-Yan Chen; Xiu-Ting Sun; Xiang Wang; Yi-Ying Yang; Hui Shi; Zhi-Sheng Yang (European Journal of Clinical Pharmacology, 2016)

The unique origin of orange carrot cultivars in China - Zhen-Guo Ma; Xiao-Ping Kong; Li-Jie Liu; Cheng-Gang Ou; Ting-Ting Sun; Zhi-Wei Zhao; Zeng-Jian Miao; Jun Rong; Fei-Yun Zhuang (Euphytica, 2016)

Clinical,biochemical and molecular analysis of five Chinese patients with Sandhoff disease - Wen Zhang; Huasong Zeng; Yonglan Huang; Ting Xie; Jipeng Zheng; Xiaoyuan Zhao; Huiying Sheng; Hongsheng Liu; Li Liu (Metabolic Brain Disease, 2016)

Advanced oxidation protein products induce chondrocyte apoptosis via receptor for advanced glycation end products-mediated, redox-dependent intrinsic apoptosis pathway - Qian Wu; Zhao-Ming Zhong; Si-Yuan Zhu; Cong-Rui Liao; Ying Pan; Ji-Huan Zeng; Shuai Zheng; Ruo-Ting Ding; Qing-Song Lin; Qing Ye; Wen-Bin Ye; Wei Li; et al. (Apoptosis, 2016)

Upregulation and Diverse Roles of TRPC3 and TRPC6 in Synaptic Reorganization of the Mossy Fiber Pathway in Temporal Lobe Epilepsy - Chang Zeng; Pinting Zhou; Ting Jiang; Chunyun Yuan; Yan Ma; Li Feng; Renkai Liu; Weiting Tang; Xiaoyan Long; Bo Xiao; Fafa Tian (Molecular Neurobiology, 2015)

Biodegradation of a biochar-modified waterborne polyacrylate membrane coating for controlled-release fertilizer and its effects on soil bacterial community profiles - Zijun Zhou; Changwen Du; Ting Li; Yazhen Shen; Yin Zeng; Jie Du; Jianmin Zhou (Environmental Science and Pollution Research, 2015)

Forest canopy height mapping over China using GLAS and MODIS data - Ting Yang; Cheng Wang; GuiCai Li; SheZhou Luo; XiaoHuan Xi; Shuai Gao; HongCheng Zeng (Science China Earth Sciences, 2015)

Effect of auxin, cytokinin and nitrogen on anthocyanin biosynthesis in callus cultures of red-fleshed apple (Malus sieversii f.niedzwetzkyana) - Xiao-Hao Ji; Yan-Ting Wang; Rui Zhang; Shu-Jing Wu; Meng-Meng An; Min Li; Chuan-Zeng Wang; Xiao-Liu Chen; Yan-Min Zhang; Xue-Sen Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Potent in vitro synergism of fusidic acid (FA) and berberine chloride (BBR) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Rong-mei Liang; Xiao-lan Yong; Yu-qin Duan; Yong-hong Tan; Ping Zeng; Zi-ying Zhou; Yan Jiang; Shi-hua Wang; Yun-ping Jiang; Xiao-chun Huang; Zhao-hui Dong; Ting-ting Hu; et al. (World Journal of Microbiology and Biotechnology, 2014)

Geochronology of magmatism and mineralization of the Daheishan giant porphyry molybdenum deposit, Jilin Province, Northeast China: constraints on ore genesis and implications for geodynamic setting - Ling-Li Zhou; Qing-Dong Zeng; Jian-Ming Liu; Henrik Friis; Zuo-Lun Zhang; Xiao-Xia Duan; Ting-Guang Lan (International Geology Review, 2014)

Study of GOLPH3: a Potential Stress-Inducible Protein from Golgi Apparatus - Ting Li; Hong You; Jie Zhang; Xiaoye Mo; Wenfang He; Yang Chen; Xiangqi Tang; Zheng Jiang; Ranran Tu; Liuwang Zeng; Wei Lu; Zhiping Hu (Molecular Neurobiology, 2014)

The role of Gracilaria lemaneiformis in eliminating the dissolved inorganic carbon released from calcification and respiration process of Chlamys farreri - Zeng Jie Jiang; Jian Guang Fang; Ting Ting Han; Yu Ze Mao; Jia Qi Li; Mei Rong Du (Journal of Applied Phycology, 2014)

Sorption of ammonium and phosphate from aqueous solution by biochar derived from phytoremediation plants - Zheng Zeng; Song-da Zhang; Ting-qiang Li; Feng-liang Zhao; Zhen-li He; He-ping Zhao; Xiao-e Yang; Hai-long Wang; Jing Zhao; Muhammad Tariq Rafiq (Journal of Zhejiang University-SCIENCE B, 2013)

A Murine Model of Hepatic Veno-occlusive Disease Induced by Allogeneic Hematopoietic Stem Cell Transplantation - Lingyu Zeng; Licai An; Ting Fang; Bin Pan; Haiying Sun; Chong Chen; Jiang Cao; Zhenyu Li; Kailin Xu (Cell Biochemistry and Biophysics, 2013)

SIRT1 is required for long-term growth of human mesenchymal stem cells - Hong-Feng Yuan; Chao Zhai; Xin-Long Yan; Dan-Dan Zhao; Jing-Xue Wang; Quan Zeng; Lin Chen; Xue Nan; Li-Juan He; Si-Ting Li; Wen Yue; Xue-Tao Pei (Journal of Molecular Medicine, 2012)

Induction of DIMBOA accumulation and systemic defense responses as a mechanism of enhanced resistance of mycorrhizal corn (Zea mays L.) to sheath blight - Yuan Yuan Song; Man Cao; Li Jun Xie; Xiao Ting Liang; Ren Sen Zeng; Yi Juan Su; Jing Hua Huang; Rui Long Wang; Shi Ming Luo (Mycorrhiza, 2011)

Levels, Seasonal Patterns, and Potential Sources of Organochlorine Pesticides in the Urban Atmosphere of Beijing, China - Lifei Zhang; Yeru Huang; Liang Dong; Shuangxin Shi; Li Zhou; Ting Zhang; Fangzhuo Mi; Liangzi Zeng; Dingding Shao (Archives of Environmental Contamination and Toxicology, 2011)

Effects of road age and distance on plant biodiversity: a case study in the Yellow River Delta of China - Sheng-Lan Zeng; Ting-Ting Zhang; Yu Gao; Zu-Tao Ouyang; Jia-Kuan Chen; Bo Li; Bin Zhao (Plant Ecology, 2011)

Meiotic nondisjunction in resynthesized Brassica napus and generation of aneuploids through microspore culture and their characterization - Jing Wen; Xin-hua Zeng; Yuan-yuan Pu; Li-ping Qi; Zai-yun Li; Jin-xing Tu; Chao-zhi Ma; Jin-xiong Shen; Ting-dong Fu (Euphytica, 2010)

Kinetic and Equilibrium Studies of Cr(VI) Biosorption by Dead Bacillus licheniformis Biomass - Ming Zhou; Yunguo Liu; Guangming Zeng; Xin Li; Weihua Xu; Ting Fan (World Journal of Microbiology and Biotechnology, 2007)